TRAVERSING THE PATH OF RECOVERY: SOCIAL REHABILITATION FOR NAPZA SURVIVORS AT THE CINTA KASIH BANGSA FOUNDATION SEMARANG INDONESIA - Kharis, Ahmad; Rizal, Derry Ahmad (JURNAL AL-IJTIMAIYYAH, 2025)
The abuse of Narcotics, Psychotropics, and Other Addictive Substances (NAPZA) is a social issue with far-reaching impacts on public health, the economy, and social stability. This study aims to analyze the implementation of social rehabilitation for NAPZA abuse survivors at the Cinta Kasih Bangsa Foundation (YCKB) in Ungaran. A qualitative research method with a descriptive approach was employed to understand the implementation of social rehabilitation programs and their impact on clients. Data were collected through in-depth interviews, participatory observations, and document analysis. Interviews were conducted with seven informants, four of whom were key informants as well as three additional informants as individual. The findings indicate that YCKB implements social rehabilitation in several stages, including screening, assessment, rehabilitation, and termination. The programs consist of counseling, psychoeducation, sports, recreation, skills training, pharmacotherapy, and spiritual development. The study reveals that these rehabilitation programs contribute to clients' physical and mental recovery, enhance social reintegration, and reduce relapse rates. However, challenges such as societal stigma and limited resources remain obstacles to optimizing rehabilitation efforts. This study recommends periodic evaluations and the strengthening of rehabilitation programs to ensure sustainability and improve the effectiveness of services for clients.